Celebrity Auto/Biography and the Construction of Ageing Selves - Priyatna, Aquarini (Universitas Negeri Semarang, 2017)
This paper investigates the notion ageing femininity as it is performed within the frame of celebrity culture which privileges youthfulness in beauty and body image. It focuses on the issues of age, the process of ageing, the significance of ageing, the impact of ageing as part of the construction of celebrity identity and femininity. Age[ing] is an important context that female celebrities need to negotiate and embrace the ways in which cultural values need to be considered as well. Looking into the portrayal of the auto/biographical subjects and the visual images used, the paper argues that celebrities negotiate, transform and extend their forms of femininity as they age. Both auto/biographies present their auto/biographical subjects to show the construction of appealing ageing celebrity femininities that are closely linked to the characteristics of the Third Agers, being fit, fashionable, functional and flexible.Â